Environmental Flow Requirements of Estuaries: Providing Resilience to Current and Future Climate and Direct Anthropogenic Changes - Chilton, Daniel; Hamilton, David P.; Nagelkerken, Ivan; Cook, Perran; Hipsey, Matthew R.; Reid, Robert; Sheaves, Marcus; Waltham, Nathan J.; Brookes, Justin (Frontiers in Environmental Science, 2021)
Estuaries host unique biodiversity and deliver a range of ecosystem services at the interface between catchment and the ocean. They are also among the most degraded ecosystems on Earth. Freshwater flow regimes drive ecological processes contributing to their biodiversity and economic value, but have been modified extensively in many systems by upstream water use. Knowledge of freshwater flow requirements for estuaries (environmental flows or E-flows) lags behind that of rivers and their floodplains. Generalising estuarine E-flows is further complicated by responses that appear to be specific to each system. Here we critically review the E-flow requirements of estuaries to i) identify the key ecosystem processes (hydrodynamics, salinity regulation, sediment dynamics, nutrient cycling and trophic transfer, and connectivity) modulated by freshwater flow regimes, ii) identify key drivers (rainfall, runoff, temperature, sea level rise and direct anthropogenic) that generate changes to the magnitude, quality and timing of flows, and iii) propose mitigation strategies (e.g., modification of dam operations and habitat restoration) to buffer against the risks of altered freshwater flows and build resilience to direct and indirect anthropogenic disturbances. These strategies support re-establishment of the natural characteristics of freshwater flow regimes which are foundational to healthy estuarine ecosystems.